2008
DOI: 10.1016/j.socscimed.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods and disability in later life

Abstract: This paper uses the US Health and Retirement Study to explore linkages between neighborhood conditions and stages of the disablement process among adults ages 55 and older in the United States. We consider multiple dimensions of the neighborhood including the built environment as well as social and economic conditions. In doing so, we use factor analysis to reduce indicators into eight neighborhood scales, which we incorporate into two-level logistic regression models along with controls for individual-level f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
147
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 46 publications
13
147
1
5
Order By: Relevance
“…Neighborhood walkability is a potentially modifiable factor that refers to how conducive the environment is to walking and has been associated with levels of physical activity, reduced risk of disability, cardiovascular disease, obesity and depression. [13][14][15][16] Key components of walkability include residential density, street pattern or connectivity, mixed land use, and pedestrian infrastructure. [15][16][17][18][19][20] The number or density of intersections, called street connectivity, captures the directness of routes between destinations and has shown to be a significant predictor of walking.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood walkability is a potentially modifiable factor that refers to how conducive the environment is to walking and has been associated with levels of physical activity, reduced risk of disability, cardiovascular disease, obesity and depression. [13][14][15][16] Key components of walkability include residential density, street pattern or connectivity, mixed land use, and pedestrian infrastructure. [15][16][17][18][19][20] The number or density of intersections, called street connectivity, captures the directness of routes between destinations and has shown to be a significant predictor of walking.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence suggests these neighborhood characteristics may contribute to obesity and diabetes [5]. Older adults may be particularly vulnerable to less favorable neighborhood environments given reduced physical function and mobility impairments [6]. By the same token, older adults can benefit from living in favorable environments.…”
mentioning
confidence: 99%
“…This was associated with many outcomes in cross-sectional research, even after adjustment for individual characteristics, including depression, [51][52][53] 67 and disability. [68][69][70][71] Other studies failed to find an association. [72][73][74] A causative role for neighbourhood disadvantage in these associations is supported by a number of longitudinal studies, which have found similar effects after accounting for individual level characteristics.…”
Section: Summary Of Epidemiologic Evidencementioning
confidence: 99%